Phylogenetic Investigation of Peptide Hormone and Growth Factor Receptors in Five Dipteran Genomes - Vogel, Kevin J.; Brown, Mark R.; Strand, Michael R. (Frontiers in Endocrinology, 2013)
Peptide hormones and growth factors bind to membrane receptors and regulate a myriad of processes in insects and other metazoans. The evolutionary relationships among characterized and un-characterized (“orphan”) receptors can provide insights into receptor-ligand biology and narrow target choices in deorphanization studies. However, the large number and low sequence conservation of these receptors make evolutionary analysis difficult. Here, we characterized the G-protein coupled receptors (GPCRs), receptor guanylyl cyclases (RGC) and protein kinase receptors (PKR) of mosquitoes and select other flies by interrogating the genomes of Aedes aegypti, Anopheles gambiae, Culex quinquefasciatus, Drosophila melanogaster, and D. mojavensis. Sequences were grouped by receptor type, clustered using the program CLANS, aligned using HMMR, and phylogenetic trees built using PhyML. Our results indicated that PKRs had relatively few orphan clades whereas GPCRs and RGCs had several. In addition, more than half of the class B secretin-like GPCRs and RGCs remained uncharacterized. Additional studies revealed that class B GPCRs exhibited more gain and loss events that other receptor types. Finally, using the neuropeptide F family of insect receptors and the neuropeptide Y family of vertebrate receptors, we also show that functional sites considered critical for ligand binding are conserved among distinct family members and between distantly related taxa. Overall, our results provide the first comprehensive analysis of peptide hormone and growth factor receptors for a major insect group.